Effect of High Velocity Deformation on Strength of ArmoredComposite Materials - et. al., Trah Quyet Thang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper considers the problem of determining the strength of carbon fiber reinforced plastic with straight and curved fibers under high-speed loading. High-speed tests of unidirectional CFRP specimens with rectilinear and wavy structure have been carried out. The influence of the structure and high-speed loading on the ultimate strength and ultimate deformation of the material is investigated. For the first time, a detailed study of the effect of fiber curvature on the properties of CFRP under high-speed deformation has been carried out. As a result of dynamic tests, it was shown that the ultimate strength in unidirectional laying is higher than in wavy laying. The effect of increasing the ultimate deformations of specimens with bent fibers was established, which was noted earlier for the case of tensile tests.